PERANCANGAN PEMBANGKIT LISTRIK TENAGA OMBAK (PLTO) BERBASIS MASSA PELAMPUNG - Basri, Muhammad Hasan (ELEMEN : JURNAL TEKNIK MESIN, 2023)
In the digital era, the need for electricity supply is very large. According to research data from the Ministry of Communication and Information, in 2019 Indonesia had a high need for electrical energy, reaching 50,000 Mega Watts. Fulfillment of renewable energy such as PLTO in Indonesia's maritime areas is still very possible. The aim of this research is to design a PLTO device using the cylinder float method on a small scale. Ocean waves will move the buoy up and down and move a series of gears and generators. The amount of lifting power (buoyancy) is influenced by the dimensions (length and width) of the cylinder float. The dimensions (length and location of inertia) of the arm also determine the amount of torque to rotate the gearbox and generator. From the results of the float mass-based PLTO design, it can be seen that on the first day of data collection the highest voltage was 16.06 V, current 0.66 A and electrical power 10.59 W, on the second day the highest voltage was 18.2 V, current 0.66 A and power electricity 10.53 W.